The Influence of Environmental Concern and Green Marketing on Purchase Decision with Environmental Knowledge as a Mediating Variable in UPVC Products in Lombok - Adam, Adytya Rahmad; Suprayadi, Didy Ika; Athar, Handry Sudiartha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to identify and analyze the influence of environmental concern and green marketing on purchase decisions for UPVC products in Lombok, with environmental knowledge serving as a mediating variable. This research employs a causal-associative design and utilizes a survey sampling method. The sample consists of 110 respondents, selected using a purposive sampling technique. The analytical tool used is SmartPLS. The results of this study indicate that environmental concern has a positive and significant effect on purchase decisions. Green marketing shows a positive but not significant effect on purchase decisions. Furthermore, environmental concern has a positive and significant effect on environmental knowledge, while green marketing also has a positive and significant effect on environmental knowledge. Environmental knowledge has a positive and significant influence on purchase decisions. Moreover, environmental knowledge positively and significantly mediates the relationship between environmental concern and purchase decisions, as well as between green marketing and purchase decisions.